The tree shepherd's daughter - Summers, Gillian (Summers, Gillian. Faire folk trilogy, 2007)
Upon the death of her mother, a Los Angeles attorney, sixteen-year-old Keelie is sent to live with her father, a woodworker at Renaissance fairs, and discovers that the odd "allergy" she has to wood is actually powerful earth magic that she must learn to control.